Effectiveness of SIAP UKGS, a digital collaborative oral health care model, among schoolchildren: a controlled pre–post study - Herry Imran; Cut Soraya; Muslim Akmal; Poppy Andriany (Aposta: Revista de Ciencias Sociales, 2026)
The School Dental Health Program (Usaha Kesehatan Gigi Sekolah, UKGS) is an important component of school-based oral health promotion and prevention. However, conventional UKGS implementation remains constrained by limited human resources, suboptimal cross-sectoral coordination, and inadequate mechanisms for continuous monitoring and follow-up. To address these limitations, the SIAP UKGS application was developed as a collaborative dental and oral health care model integrating service delivery, health education, monitoring, and coordination within the school setting. To evaluate the effectiveness of the SIAP UKGS application compared with conventional UKGS methods in improving oral health knowledge, attitudes, and practices and in reducing dental caries and oral hygiene indices among elementary school students in Banda Aceh City, Indonesia. A quasi-experimental study employing a pre–post test design with a control group was conducted among 800 elementary school students in Banda Aceh City. Participants were selected using purposive sampling and allocated to an application-based UKGS intervention group (n=400) or a conventional UKGS control group (n=400). The primary outcomes were knowledge, attitudes, practices, dental caries experience measured using the DMF-T/def-t index, and oral hygiene status measured using the Oral Hygiene Index-Simplified (OHIS). Within-group changes were assessed using paired t-tests or Wilcoxon signed-rank tests, whereas between-group differences were evaluated using independent-samples t-tests or Mann–Whitney U tests, as appropriate. The application-based UKGS group demonstrated significant improvements in knowledge (54.10 to 60.65), attitudes (55.64 to 60.13), and practices (52.21 to 57.20), accompanied by significant reductions in the DMF-T/def-t index (4.415 to 3.864) and OHIS (1.686 to 1.354) (all p